Urban development on a participatory democracy basis. How to actively involve citizens as local experts and partners in urban governance. The urban renewal program Aktives Stadtzentrum Turmstraße, Berlin. - Delatte, Aline (ibidem, 2014)
What is the role of citizens in urban development decision-making processes? In answer of this globally relevant question, the author offers a comprehensive analysis of urban renewal programs in Berlin which aim to strengthen collaborative planning between public authorities and civil society. Based on the case study of the federal urban development program Aktives Stadtzentrum Turmstraße, the author distinguishes two types of participation: Citizen participation in a time-limited and issue-oriented "top-down" participatory process; and citizen-representative involvement within local urban governance on an ongoing basis. Highlighting the drivers and barriers of participatory processes, her insights aim to strengthen citizen involvement towards a more participatory and democratic planning process. Uncovering valuable lessons to be learnt for the implementation of local participation in European cities, this timely book helps untangle the complexities of local governance involving administrations, civil society, and urban planners.
Keywords: Partizipation; Bewohnerbeteiligung; Stadtentwicklungsplanung; Stadterneuerung; Kooperation; Kommunalpolitik; Stadtteil; Urbanität; Planungsprozess; Grünfläche; Freiraumplanung; Urban Governance